Pengaruh Kompensasi dan Deskripsi Pekerjaan terhadap Etos kerja karyawan PT. BMAJ - Budianto, Budianto (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This research uses quantitative descriptive research. The total population in the study was 126 employees with the sampling technique using the Slovin formula 95% confidence level and 5% error tolerance so that from the calculations obtained as many as 96 samples. Simultaneously there is a significant effect between compensation and job description variables on the work ethic of employees of PT. BMAJ. While partially found compensation variables have a significant effect on the work ethic of employees of PT. BMAJ. Partially it was found that the job description variable had a significant effect on the work ethic of the employees of PT. BMAJ.